Prove that <munder> <mo movablelimits="true" form="prefix">lim <mrow class="MJX-TeXAtom-

Cooper Doyle 2022-07-07 Answered
Prove that
lim n + ( 1 n 1 n + 1 ) = 0
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (1)

Valeria Wolfe
Answered 2022-07-08 Author has 11 answers
you have
1 n 1 n + 1 = 1 n ( n + 1 )
and
0 1 n ( n + 1 ) 1 n 2
then because
lim n + 1 n 2 = 0
we have lim n + ( 1 n 1 n + 1 ) = 0
Did you like this example?
Subscribe for all access

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

New questions